High-Mobility Group 1/2 Proteins Are Essential for Initiating Rolling-Circle-Type DNA Replication at a Parvovirus Hairpin Origin - Cotmore, Susan F. (American Society for Microbiology, 1998)
Rolling-circle replication is initiated by a replicon-encoded endonuclease which introduces a single-strand nick into specific origin sequences, becoming covalently attached to the 5′ end of the DNA at the nick and providing a 3′ hydroxyl to prime unidirectional, leading-strand synthesis. Parvoviruses, such as minute virus of mice (MVM), have adapted this mechanism to amplify their linear single-stranded genomes by using hairpin telomeres which sequentially unfold and refold to shuttle the replication fork back and forth along the genome, creating a continuous, multimeric DNA strand. The viral initiator protein, NS1, then excises individual genomes from this continuum by nicking and reinitiating synthesis at specific origins present within the hairpin sequences. Using in vitro assays to study ATP-dependent initiation within the right-hand (5′) MVM hairpin, we have characterized a HeLa cell factor which is absolutely required to allow NS1 to nick this origin. Unlike parvovirus initiation factor (PIF), the cellular complex which activates NS1 endonuclease activity at the left-hand (3′) viral origin, the host factor which activates the right-hand hairpin elutes from phosphocellulose in high salt, has a molecular mass of around 25 kDa, and appears to bind preferentially to structured DNA, suggesting that it might be a member of the high-mobility group 1/2 (HMG1/2) protein family. This prediction was confirmed by showing that purified calf thymus HMG1 and recombinant human HMG1 or murine HMG2 could each substitute for the HeLa factor, activating the NS1 endonuclease in an origin-specific nicking reaction.